-6y=8

Move the negative in front of the fraction.

-6y=8

Multiply each term by y and simplify.

Multiply each term in -6y=8 by y.

-6y⋅y=8⋅y

Cancel the common factor of y.

Move the leading negative in -6y into the numerator.

-6y⋅y=8⋅y

Cancel the common factor.

-6y⋅y=8⋅y

Rewrite the expression.

-6=8⋅y

-6=8y

-6=8y

Rewrite the equation as 8y=-6.

8y=-6

Divide each term by 8 and simplify.

Divide each term in 8y=-6 by 8.

8y8=-68

Cancel the common factor of 8.

Cancel the common factor.

8y8=-68

Divide y by 1.

y=-68

y=-68

Simplify -68.

Cancel the common factor of -6 and 8.

Factor 2 out of -6.

y=2(-3)8

Cancel the common factors.

Factor 2 out of 8.

y=2⋅-32⋅4

Cancel the common factor.

y=2⋅-32⋅4

Rewrite the expression.

y=-34

y=-34

y=-34

Move the negative in front of the fraction.

y=-34

y=-34

y=-34

y=-34

The result can be shown in multiple forms.

Exact Form:

y=-34

Decimal Form:

y=-0.75

Solve for y -6/y=8